2014
DOI: 10.1111/1469-0691.12369
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinitis due to Gram-negative bacteria is associated with increased mortality

Abstract: The aim of this study was to describe the features of a large cohort of patients with postoperative mediastinitis, with particular regard to Gram-negative bacteria (GNB), and assess their outcome. This bicentric retrospective cohort included all patients who were hospitalized in the Intensive Care Unit with mediastinitis after cardiac surgery during a 9-year period. Three hundred and nine patients developed a mediastinitis with a mean age of 65 years and a mean standard Euroscore of six points. Ninety-one pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 23 publications
3
53
3
3
Order By: Relevance
“…In a wide range of mediastinitis in a 8-years study carried out in France (Charbonneau et al) 3 cases of Haemophilus influenzae were found; that being a percentage of 0.9% [7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a wide range of mediastinitis in a 8-years study carried out in France (Charbonneau et al) 3 cases of Haemophilus influenzae were found; that being a percentage of 0.9% [7]. …”
Section: Discussionmentioning
confidence: 99%
“…It is primarily TEM-type enzyme. A decreased susceptibility to beta-lactams by modification of the penicillin binding proteins (PBPs) target this antibiotic family is another mechanism which can add an efflux mechanism [7, 8, 10, 12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…; therefore, clinicians may not consider them a source of GNRB. According to the literature, Gram-negative organisms account for 22e28.3% of mediastinitis, 12,13 and 20e30% of surgical site infections. 3,14 This study provides evidence that several factors are associated with increased mortality from GNRB after CVS.…”
Section: Discussionmentioning
confidence: 99%
“…La mediastinitis posterior a cirugía cardíaca tiene una prevalencia que va desde el uno al dos por ciento [1][2][3][4][5][6][7] . Adicionalmente, en cirugía coronaria incrementa los costos en los hospitales hasta el 240% comparado con los procedimientos no complicados 2 .…”
Section: Introductionunclassified
“…La mediastinitis secundaria a bacterias gramnegativas está asociada a una disminución en la sobrevida, en muchas ocasiones debido a un inapropiado esquema antibiótico 3 . En estos casos, la diseminación hematógena prevalece más que la inoculación directa.…”
unclassified